2007
DOI: 10.1016/j.gie.2006.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Identifying intestinal metaplasia at the squamocolumnar junction by using optical coherence tomography

Abstract: Background-Optical coherence tomography (OCT) is an optical imaging method that produces high-resolution cross-sectional images of the esophagus. The accuracy of OCT for differentiating tissue types at the squamocolumnar junction (SCJ) has not been established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
89
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 22 publications
(17 reference statements)
3
89
0
Order By: Relevance
“…The overall average accuracy achieved by the readers was 82.6% (range, 73.7-94.7%), with good sensitivity (80.3-85.7%) and specificity (83.3-97.6%) for each of the carcinoma types over the two validation assessments. The sensitivities and specificities achieved in this study are comparable to those reported in prior studies validating OCT criteria in esophageal (23,24) and cardiovascular pathology (19).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The overall average accuracy achieved by the readers was 82.6% (range, 73.7-94.7%), with good sensitivity (80.3-85.7%) and specificity (83.3-97.6%) for each of the carcinoma types over the two validation assessments. The sensitivities and specificities achieved in this study are comparable to those reported in prior studies validating OCT criteria in esophageal (23,24) and cardiovascular pathology (19).…”
Section: Discussionsupporting
confidence: 84%
“…OCT can be used to conduct large-volume in vivo microscopy of tissue with resolutions comparable to low-power microscopy (18). OCT has been used to accurately detect and diagnose pathology in vivo for a number of years (17)(18)(19)(20)(21)(22)(23)(24) and has been used to assess the fine microarchitectural features in both normal and pathologic lung (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43).…”
mentioning
confidence: 99%
“…Laser confocal micocroscopy in 63 patients had an accuracy of 94% for detection of neoplasia (70). Optical coherence tomography which functions in a manner more similar to ultrasonography but using light to create interference patterns also has promising results for the detection of intestinal metaplasia at the gastric junction although prior studies have not been very rewarding in detecting dysplasia (71). Spectroscopic devices can analyze the light coming from the mucosa and assess its components to determine the degree of dysplasia that is present.…”
Section: Imaging In Barrett's Esophagusmentioning
confidence: 99%
“…[45][46][47][48][49][50][51][52][53] A novel ballooncentering OCT catheter was developed to conduct volumetric imaging of the entire distal esophagus (6 cm) ( Figure 1, B). 53 Squamous mucosa is characterized by the presence of layering without epithelial glands.…”
Section: Oct In Esophageal Imagingmentioning
confidence: 99%
“…53 The potential of OCT to diagnose SIM has been demonstrated in prospective studies, with sensitivities of 81% to 97% and specificities of 57% to 92%. [45][46][47][48][49][50][51][52][53] Additionally, studies have demonstrated successful grading of dysplasia with OCT. Reported sensitivities and specificities for detecting high-grade dysplasia/intramucosal carcinoma range from 54% to 83% and 72% to 75%, respectively. [45][46][47][48][49][50][51][52][53] Currently, studies are being conducted to evaluate real-time endoscopic OCT-guided biopsy with laser marking in patients.…”
Section: Oct In Esophageal Imagingmentioning
confidence: 99%